Pola Komunikasi Organisasi Divisi Human Resource And General Affair Dalam Pemeliharaan Aset Perusahaan Pada PT. Semen Bosowa Maros - Iriyanti , Hana; Majid , Abd; muttaqin, Andi (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
The purpose of this study was to determine the pattern of organizational communication used in the human resource and general affairs division in the company's asset maintenance activities at PT. Semen Bosowa Maros and what organizational communication media are used in the general affairs department in the company's asset maintenance activities at PT. Bosowa Maros Cement. This research lasted for two months using descriptive qualitative research methods whose data sources were obtained through interviews, observations and documentation by taking five staff from the human resource and general affairs division as informants and processing them and linking them using bureaucratic theory, systems theory and information theory. The results of this study indicate that the communication patterns used in the Human Resource and General Affairs division are formal communication patterns in the form of upward communication, downward communication, horizontal and diagonal communication and informal communication patterns or grapevine. The communication media used include HT (Handy Talky) used when outdoors or in the field, WA (WhatsApp) and SAP (System Application and Processing) applications.